A Question of Costs: Considering Pressure on White-Collar Criminal Defendants - Ribstein, Sarah (2009)
Because of the expense of defending white-collar criminal cases, individual corporate defendants can rarely fund their own defenses and often rely on their employers to pay their legal costs. Employers, however, often feel pressure to refuse to pay their employees' attorneys' fees. When employers decline to pay their employees' defense costs, defendants can be, in effect, coerced into pleading guilty because they do not have the financial resources to defend themselves at trial. Commentators have discussed the problem of pressure on white-collar defendants but have not traced the cause of the pressure back to one of its most basic roots: criminalizing conduct that is prohibitively expensive for an individual to defend. Others have addressed the question of whether corporate behavior has been overcriminalized but have not focused on the high cost of defending these crimes as one of the key arguments against criminalizing the behavior in the first place. This Note intertwines the two strands of the debate over corporate crime: the strand evaluating the existence of and solutions to pressure on individual white-collar defendants and the strand questioning the overcriminalization of corporate law. This Note adds to both strands by focusing on one aspect, high defense costs, that contributes to the pressure, makes it unique to corporate crime as opposed to street crime, and puts it out of the reach of commonly suggested procedural fixes. The Note concludes that white-collar criminal prosecutions inherently place financial pressure on defendants, and legislatures should consider this pressure when deciding what behavior to criminalize